2008
DOI: 10.1093/cvr/cvn082
|View full text |Cite
|
Sign up to set email alerts
|

Influence of postprandial triglyceride-rich lipoproteins on lipid-mediated gene expression in smooth muscle cells of the human coronary artery

Abstract: The pathophysiological contribution of TRL to the development of atherosclerosis and the stability of atherosclerotic plaques may depend on the fatty acid composition of TRL. Our findings suggest a role for macrophage-inhibiting cytokine-1 (MIC-1) in coronary artery cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 29 publications
2
56
0
2
Order By: Relevance
“…However, its biological character and current knowledge about its effects in humans suggested that it might play an important role in the development and progression of inflammatory and atherosclerotic Table 4 Relationships of serum macrophage inhibitory cytokine-1 (MIC-1; pg/ml) with other anthropometric, hormonal, and biochemical parameters calculated in a combined population of all three study groups (A, nZ54) and in the combined group of obese patients (B and C, nZ31) both before and after very low calorie diet program (VLCD). processes and cancer (7,10,12). Recent data indicated a direct role for MIC-1 in energy homeostasis regulation in cachectic conditions making it a potentially interesting candidate molecule to modulate food intake and/or body adiposity (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its biological character and current knowledge about its effects in humans suggested that it might play an important role in the development and progression of inflammatory and atherosclerotic Table 4 Relationships of serum macrophage inhibitory cytokine-1 (MIC-1; pg/ml) with other anthropometric, hormonal, and biochemical parameters calculated in a combined population of all three study groups (A, nZ54) and in the combined group of obese patients (B and C, nZ31) both before and after very low calorie diet program (VLCD). processes and cancer (7,10,12). Recent data indicated a direct role for MIC-1 in energy homeostasis regulation in cachectic conditions making it a potentially interesting candidate molecule to modulate food intake and/or body adiposity (14).…”
Section: Discussionmentioning
confidence: 99%
“…MIC-1 was also identified as a predictor of cardiovascular events in a cohort of previously healthy women (11,12) and as an early mediator of the injury response in kidney and lung (13). Recently, a key role of increased MIC-1 concentrations in the induction of cancer-related anorexia and weight loss in animals and humans was described (14).…”
Section: Introductionmentioning
confidence: 99%
“…Other cardiovascular cell types, including endothelial cells, vascular smooth muscle cells, and adipocytes, have been shown to produce GDF-15 under stressful conditions. [12][13][14] Moreover, GDF-15 has been detected in atherosclerotic plaque macrophages, where it may be induced by oxidized low-density lipoprotein and proinflammatory cytokines. 3,6 Accumulating evidence indicates that circulating levels of GDF-15 are associated with prognosis in patients with cardiovascular disease.…”
Section: Clinical Perspective On P 1395mentioning
confidence: 99%
“…Under normal physiologic conditions, GDF15 is weakly expressed by most tissues [8,9]. However, following injury, ischemia, and other forms of oxidative and/or metabolic stress, its production is potently upregulated by a wide range of tissues including activated macrophages, cardiomyocytes, and vascular smooth muscle cells [10,11,12]. In large population-based studies, GDF15 has been associated with endothelial dysfunction, atherosclerosis, left ventricular hypertrophy, and impaired systolic function, independent of cardiovascular risk factors such as inflammatory markers (e.g., C-reactive protein) [13,14].…”
Section: Introductionmentioning
confidence: 99%